Reactive Rather than Proactive Diabetes Management in the Perioperative Period - Hommel, Inge; van Gurp, Petra J.; den Broeder, Alfons A.; Wollersheim, Hub; Atsma, Femke; Hulscher, Marlies E. J. L.; Tack, Cees J. (Hormone and Metabolic Research, 2017)
As perioperative hyperglycemia is associated with poor postoperative patient outcomes, clinical guidelines provide recommendations for optimal perioperative glucose control. It is unclear to what extent recommended glucose levels are met in daily practice, and little is known about factors that influence these levels. We describe blood glucose levels throughout the hospital care pathway in 375 non-critically ill patients with diabetes who underwent major surgery (abdominal, cardiac, or orthopedic) in 6 hospitals, examine determinants of these levels including adherence to 9 quality indicators for optimal perioperative diabetes care, and perform qualitative interviews to identify barriers for optimal care. Virtually all patients (95%) experienced at least one hyperglycemic value (>10 mmol/l); 9% had at least one value <4 mmol/l. Mean glucose increased from preoperative to postoperative day (POD) 1 (+2.3 mmol/l, 5–95% CI 1.9–2.7), and then gradually decreased on POD 2–14 (+1.8 mmol/l, 5–95% CI 1.4–2.2). Insulin-treated patients (with or without oral agents) had higher glucose levels (+1.7 mmol/l, 5–95% CI 0.5–3.0, and +1.2 mmol/l, −0.1 to −2.5) than patients using oral agents only. Indicator adherence tended to be associated with higher glucose levels. Barriers for optimal care included a lack of formalized agreements on target glucose levels, absence of directly obvious disadvantages of hyperglycemia, and concern about inducing hypoglycemia. Hyperglycemia is common after major surgery, in particular on POD1 and in insulin-treated patients. Our results suggest that perioperative diabetes care is reactive rather than proactive, and that current emphasis of professionals is on treating instead of preventing postoperative hyperglycemia.
Keywords: diabetes mellitus type 1; diabetes mellitus type 2; diabetes complication; glucose